Multiple Aspects of PIP2 Involvement in C. elegans Gametogenesis - Ulicna, Livia; Rohozkova, Jana; Hozak, Pavel (International journal of molecular sciences, 2018)
One of the most studied phosphoinositides is phosphatidylinositol 4,5-bisphosphate (PIP2), which localizes to the plasma membrane, nuclear speckles, small foci in the nucleoplasm, and to the nucleolus in mammalian cells. Here, we show that PIP2 also localizes to the nucleus in prophase I, during the gametogenesis of C. elegans hermaphrodite. The depletion of PIP2 by type I PIP kinase (PPK-1) kinase RNA interference results in an altered chromosome structure and leads to various defects during meiotic progression. We observed a decreased brood size and aneuploidy in progeny, defects in synapsis, and crossover formation. The altered chromosome structure is reflected in the increased transcription activity of a tightly regulated process in prophase I. To elucidate the involvement of PIP2 in the processes during the C. elegans development, we identified the PIP2-binding partners, leucine-rich repeat (LRR-1) protein and proteasome subunit beta 4 (PBS-4), pointing to its involvement in the ubiquitin⁻proteasome pathway.
Keywords: Proteasome Endopeptidase Complex; RNA interference; Meiotic Prophase I; Chromosomes; proteiny s repeticemi bohatými na leucin; Animals; C. elegans; proteasomový endopeptidasový komplex; hermafroditické organismy; Phosphotransferases (Alcohol Group Acceptor); nucleus; fosfotransferasy s alkoholovou skupinou jako akceptorem; Gene Expression Regulation, Developmental; fosfatidylinositol-4,5-difosfát; Hermaphroditic Organisms; vývojová regulace genové exprese; RNA Interference; Phosphatidylinositol 4,5-Diphosphate; buněčné jádro; Cell Nucleus; Leucine-Rich Repeat Proteins; phosphatidylinositol 4,5-bisphosphate; Caenorhabditis elegans Proteins; Caenorhabditis elegans; Gametogenesis; zvířata; Proteins; proteiny Caenorhabditis elegans; proteiny; gametogeneze; PPK-1; profáze meiózy I; chromozomy